Catarrhal mastitis by Staphylococcus simulans in a nulliparous goat - de Moura, Guilherme Santana; Marques, Michele Flávia Sousa; de Souza, Fernando Nogueira; da Costa, Luciana Bignardi Brisola Casimiro; Acosta Abad, Atzel Candido; Mota, Rinaldo Aparecido (Brazilian Journal of Veterinary Research and Animal Science, 2018)
The present paper is a case report of a one-year old nulliparous Alpine Goat belonging to a dairy goat farm in semi-arid region of Brazil. Both glands were naturally infected by α-hemolytic Staphylococcus simulans and evolved similar clinical signs. The mammary glands presented an acute catarrhal mastitis with systemic clinical signs that responded positively to treatment with gentamicin associated with amoxicillin. The present report suggests the importance of the pathogenic potential of non-aureus Staphylococci strains (NAS) as a cause of clinical mastitis also in nulliparous animals. The isolate showed resistance to tetracycline and contained staphylococcal toxin production genes (sec, sec and TSST-1). Moreover, it has been reported that Staphylococcus simulans is an emerging pathogen in humans causing cutaneous and osteoarticular infections, mainly in those in close contact with farm animals. To the best of our knowledge, this is the first report of a clinical mastitis in a nulliparous goat caused by Staphylococcus simulans.